Aplicación de Instrumentos Pedagógicos como Estrategias Didácticas para el Desarrollo de Destrezas con Criterio de Desempeño en el Área de Ciencias Naturales del Décimo Año del “Ites” Carlos Cisneros Periodo 2012-2013 - Alcocer Yungán, Luis Fredy (2016)
A methodological proposal was designed and implemented in the research, which was the basis for learning of the subject of Natural Sciences, of the students of tenth year of the ITES "Carlos Cisneros" from Riobamba city. The objective was to design and implement educational tools like didactic strategies for the development of skills with performance criteria in the area of Natural Sciences. The theoretical foundations are characterized by explaining of practical form application of educational tools supported by constructivism, learning to learn. Pedagogical tools proposed are graphic organizers, technique of cause and effect, attributes wheel, map of ideas, concept maps, mentefacts, etc. The proposed methodology of work is experimental because it was applied the didactic guide called "Instrumentos pedagogicos como estrategias didacticas para el desarrollo del aprendizaje en la asignatura de Ciencias Naturales". The conclusions reflect the results achieved of students of tenth year of ITES "Carlos Cisneros", showing that 38.00% always, 60.7%) sometimes, and 1.3 % never of students surveyed report that teachers use educational tools, showing an average of 33.33% of respondents indicate that educational tools if used. It concluded that educational tools are pedagogical tools used by teachers to develop skills with performance criteria; it can say that learning becomes attractive when several resources for learning are combined.